Utilization of Customer Entrepreneurs as a Strategy to Improve Business Performance Performance of Micro, Small and Medium Enterprises (MSMEs) - Khalik, Idham; Siregar, Ade Perdana (Dinasti International Journal of Management Science, 2025)
The role of MSMEs is important in economic growth in Indonesia, it can improve people's welfare. Indonesian MSMEs contribute to Gross Domestic Product and national exports. Utilizing consumer participation in marketing is a strategy that can be carried out by following technological developments. Implementing consumer utilization requires consideration of customer knowledge management, entrepreneurial collaborative capability and customer network quality so that business performance increases. The aim of this research is to examine the role of customer knowledge management, entrepreneurial collaborative capability and customer network quality in mediating the influence of customer entrepreneurship on MSME business performance. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The research results are (1) customer knowledge management as a mediating influence of customer entrepreneurs has a significant positive effect on MSME business performance; (2) customer network quality as a mediating influence of customer entrepreneurs has a significant positive effect on MSME business performance; (3) entrepreneurial collaborative capability as a mediating influence of customer entrepreneurship has a significant positive effect on MSME business performance.